ChemInform Abstract: One Hundred Years of Vitamins — A Success Story of the Natural Sciences. Issue 17 (4th April 2013) - Eggersdorfer, Manfred; Laudert, Dietmar; Letinois, Ulla; McClymont, Tom; Medlock, Jonathan; Netscher, Thomas; Bonrath, Werner
Abstract Review: 316 refs.